Combined catalyst, preparation method, application and method for preparing p-hydroxybenzaldehyde through catalytic oxidation of p-methylphenol under non-alkali condition
By using a combination of PtFe/C and Pd/C or PtFe/C and Pd/S-C catalysts to catalyze oxidation under non-base conditions, the problem of low yield in p-cresol catalytic oxidation process and easy catalyst poisoning is solved, and p-cresol is achieved The effect of efficient conversion to aldehydes reduces production costs and separation complexity.
Patent Information
- Application Number
- CN202411417747.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The current p-cresol catalytic oxidation process has low product yield, a large amount of soluble alkali is required, and the catalyst is easily poisoned. The use of flammable and explosive methanol solvents has low catalyst activity and high cost, and the separation process is complex, resulting in high production costs.
Using a combined catalyst composed of PtFe/C and Pd/C or PtFe/C and Pd/S-C, the interlayer ordered nano alloy and sub-nano cluster catalyst are prepared efficiently to achieve efficient catalytic oxidation under non-alkali conditions and avoid Using methanol and soluble bases improves catalyst activity and selectivity.
The efficient conversion of p-cresol to p-hydroxyaldehyde under alkali-free conditions improves yield and selectivity, reduces production costs, avoids catalyst poisoning and separation complexity, and improves catalyst stability and safety.
Smart Images

Figure CN119215931A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of p-hydroxyaldehyde preparation, and in particular to a combined catalyst, a preparation method, an application and a method for preparing p-hydroxybenzaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions. Background Art
[0002] The oxidation reaction of p-cresol (hereinafter referred to as p-cresol) is of significant importance in the industrial field, and its main oxidation product, such as p-hydroxybenzaldehyde (hereinafter referred to as p-hydroxyaldehyde), has a wide range of uses in industrial applications. It is a key intermediate in the production of vanillin (a widely used flavoring agent), trimethoxybenzaldehyde, various agrochemicals, and semi-synthetic drugs such as penicillin, amoxicillin and trimethoxybenzamide. In addition, p-hydroxyaldehyde can also be used as a whitening agent for metal electroplating, an additive for perfumes and liquid crystals, showing broad application potential. Typical methods for the synthesis of p-hydroxyaldehyde from p-cresol include p-toluene esterification, Mn2O3 oxidation, transition metal salt catalytic oxidation, Etard oxidation and electrochemical oxidation. Currently, the most cost-effective method is transition metal salt catalytic oxidation.
[0003] Transition metal catalytic oxidation methods, such as using cobalt (Co) salts as homogeneous or heterogeneous catalysts, or nano-alloy composite catalysts formed by cobalt salts and manganese (Mn), copper (Cu), cerium (Ce), and metal porphyrin catalysts (such as iron-based porphyrin and cobalt-based porphyrin, etc.), usually use methanol as the reaction solvent. In the reaction system, a strong base (usually sodium hydroxide) equivalent to 2.5 to 5 times the equivalent of the reaction substrate is added to activate p-cresol and convert it into phenolate. Under the conditions of oxygen or flowing air, and at appropriate reaction temperature and residence time, the reaction can be completed to produce p-hydroxyaldehyde. The selectivity and yield of the product are usually between 70% and 95%; however, other by-products are mainly tars formed by dimers or polymers of p-cresol, which brings great difficulties to the separation of the target product and is easily adsorbed on the catalyst surface, resulting in catalyst poisoning, reduced catalytic activity, or even complete loss.
[0004] In the alkaline ethylene glycol reaction solvent, the researchers used cobalt chloride homogeneous catalysts or cobalt-copper nanoalloy heterogeneous catalysts, and with the addition of sodium hydroxide three times the amount of p-cresol, they used flowing 40 mL / min oxygen as an oxidant and conducted an 18-hour intermittent reaction study at a reaction temperature of 100 °C. The highest yield of p-hydroxyaldehyde was 74.8%; other by-products were also mainly tars formed by dimers or polymers of p-cresol, which brought great difficulties to the separation of the target product and were easily adsorbed on the catalyst surface, resulting in catalyst poisoning, reduced catalytic activity, or even complete loss of activity.
[0005] In an acidic ethylene glycol reaction solvent (a mixed solvent of 30% acetic acid and 70% ethylene glycol), a 24-hour intermittent reaction study was conducted using commercially available 5wt% Pd / C as a catalyst, a flowing oxygen atmosphere of 40 mL / min, and 100 °C. Under the optimal reaction conditions, a 73.9% conversion rate of p-cresol and a 52.7% yield of p-hydroxyaldehyde were achieved. Other by-products include a small amount of p-cresol oxidation intermediates (1-2% p-hydroxybenzyl alcohol), over-oxidation products (3.8% p-hydroxybenzoic acid), ether compounds (15-50%) generated by p-cresol and ethylene glycol, and tars formed by p-cresol dimers and polymers that are difficult to measure. However, tars have obvious catalyst poisoning effects, which makes it difficult to separate the products.
[0006] In the process of catalytic oxidation of p-cresol to prepare p-hydroxyaldehyde, 50 wt.% acetic acid aqueous solution was used as the reaction liquid, and Pt / C, Pd / C or palladium acetate was used as the catalyst. Although 100% p-cresol conversion rate was achieved, the p-hydroxyaldehyde yield was only 35% at most, and most of the p-cresol underwent dimerization or polymerization, and finally existed in the form of tar. The reason is that the catalyst selectivity of the combination of Pt / C, Pd / C or palladium acetate is low, resulting in serious side reactions, and the catalyst is quickly adsorbed by the generated tar, which further leads to catalyst deactivation; this combination proves that the Pt and Pd combination catalyst has certain catalytic activity, but the selectivity of the target product is very low.
[0007] In addition, in the existing process of preparing p-hydroxyaldehyde from p-cresol, the oxidation reaction starting from p-cresol still faces several challenges: 1) Although methanol is a commonly used reaction solvent in laboratory research and industrial production due to its low viscosity, high oxygen solubility and low boiling point, it is a flammable, explosive and low boiling point organic solvent. The explosion limit of methanol is approximately between 6% and 36.5%, and there are significant safety hazards under aerobic and high-temperature catalytic oxidation conditions; 2) In the reaction system of highly selective catalytic oxidation of p-cresol to prepare p-hydroxyaldehyde, it is usually necessary to add an excess of soluble alkali (2.5-5 times the equivalent of the substrate). This not only requires the reaction equipment to have the characteristics of alkali corrosion resistance, but also puts higher requirements on the stability of the catalyst in a strong alkaline solution. The target product exists in the form of sodium salt. In order to obtain p-hydroxyaldehyde, an excess of acid must be used to neutralize the alkali in the reaction system and convert the sodium salt form of p-hydroxyaldehyde into the product. This process produces excessive amounts of low-value waste salts, which increases the complexity of the product production process and raises production costs; 3) The selectivity for hydroxyaldehyde is usually between 70-95%, and the generation of by-products requires separation by distillation, extraction, or a combination thereof (such as extractive distillation, azeotropic distillation, etc.), which makes the subsequent separation and purification of products difficult and costly. In particular, the generation of reactant dimers and tar phenomena during catalytic oxidation poses greater challenges to product separation and refining. The introduction of excess soluble bases into the reaction system increases the number and complexity of reaction separation components, further increasing the cost of the product refining steps, thereby increasing the production cost of hydroxyaldehyde; 4) Existing transition metal catalysts, such as Co, Cu, Ce, or a combination thereof, have low activity, resulting in increased reaction temperature, prolonged required reaction time, and reduced selectivity of the target product for hydroxyaldehyde, which is also one of the reasons for the high separation cost. The limitation of catalyst activity leads to an increase in the frequency of catalytic conversion, and the corresponding equipment investment is also large; 5) In the system using commercially available Pd / C (5 wt.%) as a catalyst, the amount of Pd precious metal is high and expensive, the activity is limited, and there is a great risk of spontaneous combustion. The direct use of Pd / C in an organic solvent mixture (such as ethylene glycol-acetic acid mixture) has a great risk of explosion. In a simple Pd / C catalytic system, the activity and selectivity of Pd / C are low, resulting in a large amount (20-50 mol.%) of direct ether side reaction between p-cresol and ethylene glycol. However, the Pt / C and Pd / C combined catalysts in existing studies have too low catalytic selectivity, generate too much tar products, resulting in poor selectivity for the target product, and making it difficult to separate the target product. Ether products or tar by-products are easily adsorbed on the surface of heterogeneous catalysts, resulting in catalyst poisoning, reduced activity or even complete loss of activity. Summary of the invention
[0008] In view of this, the purpose of the present invention is to provide a combined catalyst, a preparation method, an application and a method for preparing p-hydroxybenzaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions, so as to solve the problems of low product yield, the need to add a large amount of soluble base and easy poisoning of the catalyst in the existing process of catalyzing p-cresol to prepare p-hydroxybenzaldehyde, and the problem that the organic solvent used is flammable and explosive.
[0009] Objective problems existing in the existing catalytic oxidation process of p-cresol include: (1) the need to use methanol solvent, which is flammable and explosive; (2) the need to use an excessive amount of soluble base to ensure the conversion rate of p-cresol and the selectivity for p-hydroxyaldehyde; (3) under acidic conditions, the selectivity of Pt / C and Pd / C is low, the yield of p-hydroxyaldehyde is too low, the amount of tar produced is large, and the catalyst is easily deactivated; (4) the ordinary Pd / C catalyst uses a large amount of precious metal Pd, the cost is high, and there is a flammable risk in the organic oxidation system.
[0010] The technical solution adopted by the present invention is as follows: A combined catalyst consists of a PtFe / C catalyst and a Pd / C catalyst or consists of a PtFe / C catalyst and a Pd / SC catalyst.
[0011] Among them, Pt represents platinum element, Fe represents iron element, C represents carbon element, Pd represents palladium element, and S represents sulfur element.
[0012] Preferably, the PtFe / C catalyst is a nano alloy catalyst with ordered interlayers.
[0013] Preferably, the Pd / SC catalyst is selected from Pd1 / SC catalyst (Pd single atom), Pd NC / SC catalyst (fully exposed Pd nanoclusters) and Pd NP / SC catalyst (Pd nanoparticles).
[0014] Preferably, the mass ratio of the PtFe / C catalyst to the Pd / C catalyst is 5:1 to 1:5.
[0015] Preferably, the mass ratio of the PtFe / C catalyst to the Pd / SC catalyst is 5:1 to 1:5.
[0016] Among them, Pd1 represents a single Pd atom; Pd NC indicates fully exposed sub-nanometer clusters of Pd; NP represents Pd nanoparticles. The loading of Pd1 / SC catalyst is controllable between 1 wt.% and 5 wt.%. NC / SC catalyst and Pd NP The particle size of the SC / SC catalyst is controllable.
[0017] The present invention also provides a method for preparing a combined catalyst, comprising the following steps: Dissolving iron salt in water to obtain an iron salt solution; dissolving a pyridine compound in an organic solvent to obtain a pyridine solution; mixing the iron salt solution and the pyridine solution to obtain a complex solution; Adding platinum acid solution into the complex solution to obtain a PtFe compound; The PtFe compound is dispersed in water, and then a carbon source is added, mixed and dried, and subjected to a first heat treatment to obtain a PtFe / C catalyst; The PtFe / C catalyst is mixed with the Pd / C catalyst to obtain a combined catalyst.
[0018] The present invention also provides a method for preparing a combined catalyst, comprising the following steps: Mesoscopic SC supports were prepared by cobalt-assisted carbonization of molecular precursors; The mesoscopic SC support is dispersed in water and a palladium salt solution is added to obtain a precursor; The precursor is subjected to a second heat treatment to obtain a Pd / SC catalyst.
[0019] Through an efficient and convenient method, palladium single atoms with different loading amounts, palladium fully exposed sub-nano clusters with different particle size distributions, and palladium nanoparticle catalysts were prepared. In particular, the Pd fully exposed sub-nano cluster catalyst showed the highest Pd atom utilization and the highest catalytic conversion frequency based on Pd atoms, and constructed surface active sites with the most matched energy levels for the adsorption and conversion of specific reactants / intermediates. This feature significantly improves the efficiency of the palladium active center in the catalyst, thereby enhancing the activity of the catalytic reaction.
[0020] Preferably, the pyridine compound is at least one selected from pyridine, 2,2'-bipyridine and 2,2':6',2''-tripyridine.
[0021] Preferably, the iron salt is selected from at least one of ferrous sulfate, ferrous chloride, ferrous nitrate and ferrous sulfate heptahydrate.
[0022] Preferably, the carbon source is selected from commercially available activated carbon or carbon material carrier.
[0023] Preferably, the platinum acid solution is selected from at least one of chloroplatinic acid solution, chloroplatinic acid hexahydrate and potassium chloroplatinate solution.
[0024] Preferably, the temperature of the first heat treatment is 500°C~900°C, the heating method is programmed heating, and the heating rate is 5°C / min~10°C / min; the time of the first heat treatment is 3 h~6 h; the first heat treatment is carried out in a mixed atmosphere of hydrogen and inert gas.
[0025] Preferably, the temperature of the first heat treatment is 700°C, the heating method is programmed heating, the heating rate is 5°C / min, and the time of the first heat treatment is 6 hours.
[0026] Preferably, the organic solvent is selected from ethanol.
[0027] Preferably, the preparation method of the mesoscopic SC carrier comprises the following steps: adding 2,2-dithiophene, silicon dioxide and cobalt salt to a tetrahydrofuran solution, mixing and drying to obtain a powder; heating the powder for carbonization, alkaline etching and a third heat treatment, and drying to obtain the mesoscopic SC carrier.
[0028] Preferably, the preparation method of the mesoscopic SC carrier comprises the following steps: adding 2,2-dithiophene, silicon dioxide and cobalt salt to a tetrahydrofuran solution, stirring at room temperature for 6 hours to form a uniform mixture, and then removing the solvent by rotary evaporation to obtain a powder; carbonizing the powder at a temperature of 800°C, a heating rate of 5°C / min, and a N2 atmosphere for 2 hours; alkaline etching the carbonized product with 2 M NaOH for 3 days; continuously heating with 0.5 M H2SO4 at a temperature of 90°C for 6 hours, and drying at a temperature of 85°C overnight to obtain the mesoscopic SC carrier.
[0029] Preferably, the palladium salt is selected from at least one of palladium chloride, palladium nitrate and palladium acetate.
[0030] Preferably, the temperature of the second heat treatment is 250°C to 500°C, the heating method is programmed heating, and the heating rate is 5°C / min to 10°C / min.
[0031] Preferably, the precursor is treated at a temperature of 500° C. for 3 h in a mixed atmosphere of hydrogen and inert gas to obtain Pd NP / SC catalyst; the heating method is programmed heating, and the heating rate is 5 ℃ / min.
[0032] Preferably, the precursor is treated at 450° C. for 3 h in a mixed atmosphere of hydrogen and inert gas to obtain Pd NP / SC catalyst; the heating method is programmed heating, and the heating rate is 5 ℃ / min.
[0033] Preferably, the precursor is treated at 350° C. for 3 h in a mixed atmosphere of hydrogen and inert gas to obtain Pd NC / SC catalyst; the heating method is programmed heating, and the heating rate is 5 ℃ / min.
[0034] Preferably, in a mixed atmosphere of hydrogen and inert gas, the precursor is heat-treated at 250° C. for 2 h to obtain a Pd1 / SC catalyst; the heating method is programmed heating at a heating rate of 5° C. / min.
[0035] PtFe / C catalysts with Pd single atoms Pd1 / SC and Pd fully exposed sub-nano clusters Pd NC / SC, Pd nanoparticles NP The synergistic effect of the combined catalyst of / SC promotes the reduction activation of oxygen, realizes the precise adsorption control of intermediates at active sites and the synergistic effect of oxidation steps at each level. The combination of these innovative technologies makes it possible to catalyze the oxidation of p-cresol to prepare p-hydroxyaldehyde efficiently, safely and highly selectively under completely non-alkaline conditions. Laboratory tests have verified the effectiveness and stability of the catalyst in intermittent catalytic oxidation processes and continuous catalytic oxidation processes.
[0036] The present invention also provides an application of a combined catalyst, wherein the combined catalyst is used for catalyzing p-cresol to prepare p-hydroxyaldehyde.
[0037] The present invention also provides a method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions, comprising the following steps: p-Cresol and the combined catalyst of the present invention are added to a mixed solvent containing no methanol and no soluble alkali, 0.5 Mpa of oxygen or air is introduced, the reaction mixture is heated, and maintained at 70°C-100°C for 3-6 hours, and then sampling and analysis are performed to obtain p-hydroxyaldehyde.
[0038] According to the above technical means, by using the combined catalyst of the present invention for catalytic preparation of p-hydroxyaldehyde, efficient catalytic oxidation of p-cresol to prepare p-hydroxyaldehyde under completely non-alkali conditions is achieved. Under completely non-alkali conditions, the catalyst can efficiently catalytically oxidize p-cresol and convert it into p-hydroxyaldehyde. This process is not only safe and stable, but also highly efficient. From the perspective of atomic structure, the present invention constructs a PtFe interlayer ordered nanoalloy (PtFe / C), and then accurately regulates the atomic structure and electronic structure of the active center of the heterogeneous supported PtFe nanoalloy catalyst. This allows the construction of an electronic energy state that is more matched with the antibonding orbital energy level of the activated substrate molecule O2 during the catalytic oxidation process, while ensuring the appropriate adsorption of the reaction substrate (such as p-cresol, phenoloxyl radicals, benzyloxyl radicals), thereby promoting the efficient reduction activation of O2 molecules and participating in the oxidation process of p-cresol at all levels.
[0039] In terms of Pd-based catalysts, the present invention prepares palladium single atoms, palladium fully exposed sub-nano clusters, and palladium nanoparticle catalysts with controllable particle size in the range of 1.0 wt.%-5.0 wt.%. Different from the "top adsorption" of O2 molecules by Pd1 sites in Pd1 / SC, Pd sites in Pd fully exposed sub-nano clusters or Pd nanoparticles can provide a more favorable "bridge adsorption" form of O2, providing higher O2 adsorption and reduction activation activity. In particular, Pd fully exposed sub-nano cluster catalysts can provide catalytic sites with nearly 100% Pd atomic utilization efficiency, which significantly improves the catalytic conversion frequency and catalytic activity of Pd active centers in Pd catalysts. .
[0040] Combining PtFe / C and Pd-based catalysts with different particle size distributions, the present invention realizes the research on the preparation of p-hydroxyaldehyde by catalytic oxidation of p-cresol under completely alkali-free conditions in an aqueous reaction medium. In a relatively short reaction time, the conversion rate of p-cresol can reach 100%, and the yield of p-hydroxyaldehyde exceeds 99%. In the intermittent use process, after the catalyst is recycled for 5 times, the selectivity of the target product is not significantly reduced. In a continuous flow reactor, using continuously flowing air as an oxidant, the catalytic system further realizes the continuous production of p-hydroxyaldehyde with high selectivity of p-cresol. In the continuous oxidation process, the selectivity of the target product p-hydroxyaldehyde at the reactor outlet is maintained at more than 91% within 72 hours, and the catalyst is not significantly deactivated during the continuous 72 hours of use.
[0041] Preferably, the organic solvent not containing methanol is selected from at least one of ethylene glycol, acetic acid and acetonitrile.
[0042] Preferably, the methanol-free organic solvent is selected from a mixture of ethylene glycol, acetic acid and water.
[0043] Preferably, the methanol-free organic solvent is selected from a mixture of acetonitrile, acetic acid and water.
[0044] The present invention also provides a para-hydroxyaldehyde prepared by the preparation method of the present invention.
[0045] Beneficial effects of the present invention: The combined catalyst of the present invention is constructed from a PtFe / C interlayer ordered nano alloy catalyst and a Pd-based catalyst of different particle sizes. The Pd sub-nano cluster catalyst in the combined catalyst can provide abundant catalytic sites to ensure the maximum utilization efficiency of metal atoms; the highly dispersed sub-nano fully exposed clusters allow all metal atoms to be fully exposed, so that they can be used to adsorb and convert reactants, significantly improving the efficiency of the active center in the Pd catalyst; by regulating the atomic structure and electronic structure of the active center, the catalyst achieves efficient reduction and activation of oxygen, and properly adsorbs the substrate and intermediates at all levels; the oxidation steps at all levels synergize to show excellent activity and stability. Moreover, the combined catalyst still maintains a high conversion rate and yield of raw materials and products under recycling, showing excellent stability, and successfully achieves high selectivity for the preparation of para-hydroxyaldehyde from para-cresol; The method for preparing p-hydroxyaldehyde by catalytic oxidation of p-cresol under non-alkaline conditions of the present invention does not need to use excessive acid to neutralize the residual alkali in the reaction system by catalytic oxidation of p-cresol under non-alkaline conditions, and avoids the p-hydroxyaldehyde in the form of sodium salt, thereby simplifying the separation and purification process of subsequent products, and does not produce a large amount of low-value byproduct salts, which significantly reduces the requirements for reaction equipment; abandons flammable and explosive methanol with a low boiling point as a reaction solvent, and instead adopts a more stable and safe ethylene glycol (acetonitrile) / acetic acid / water mixed solvent system; under a shorter reaction time and a lower reaction temperature, the conversion rate of p-cresol can reach 100%, and the yield of p-hydroxyaldehyde is as high as 99%. The method realizes the efficient conversion of p-cresol to p-hydroxyaldehyde, and has significant promotion and application potential in the technical field of preparation of p-hydroxyaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 TEM image of PtFe / C catalyst; Figure 2 is the XPS spectrum of PtFe / C catalyst; Figure 3 is the XRD pattern of PtFe / C catalyst; Figure 4 Pd under 500℃ heat treatment NP / SC catalyst XPS spectrum of Pd 3d electron binding energy fine spectrum; Figure 5 is the Pd obtained in Example 3 NP TEM image of / SC catalyst; Figure 6 The smaller particle size of Pd prepared in Example 2 NP HAADF-STEM image of / SC catalyst; Figure 7XRD spectra of Pd / SC catalysts obtained at different heat treatment temperatures in Examples 2 to 5; Figure 8 Pd NC HAADF-STEM image of / SC catalyst; Fig. 9 Pd NC XPS spectrum of / SC catalyst; Fig.10 HAADF-STEM image of Pd1 / SC catalyst; Fig.11 In the study of intermittent reaction process, PtFe / C and Pd NC / SC catalyst 5 times the reaction conversion rate and product yield results; Fig.12 PtFe / C and Pd NC / SC catalyst in the continuous tank reactor during the evaluation process of the reactor outlet reactant conversion rate and product yield changes. DETAILED DESCRIPTION
[0047] The following will describe the embodiments of the present invention with reference to the preferred embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0048] If no specific techniques or conditions are specified in the specific embodiments, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0049] The preparation method of PtFe / C catalyst comprises the following steps: S1. Dissolve 0.5 mmol of FeSO4·7H2O in 15 mL of deionized water to obtain an iron salt solution; S2, dissolving 1.5 mmol of 2,2'-bipyridine in 15 mL of ethanol to obtain a pyridine solution; S3, mixing the iron salt solution obtained in S1 and the pyridine solution obtained in S2 to form a deep red [Fe(bpy)3]SO4, and stirring at room temperature overnight to obtain a complex solution; S4. Add 0.5 mmol H2PtCl6·6H2O solution to the complex solution prepared in S3, stir at room temperature for 5 h, and centrifuge at 10000 rpm for 10 minutes to obtain a red precipitate; wash the red precipitate with ethanol for multiple times, and obtain a solid precipitate after centrifugation; dry the solid precipitate in an oven at 40°C overnight; grind the dried precipitate to obtain a PtFe compound; S5, dispersing the PtFe compound obtained in S4 in 50 mL of deionized water, then ultrasonically treating for 20 min, stirring for 2 h, adding 2385 mg of activated carbon; after mixing for 2 hours, drying at 40 °C overnight to obtain a mixture; S6. Place the mixture obtained in S5 in a mixed atmosphere of hydrogen and argon (the volume percentage of hydrogen is 5 vol%), heat it to 700 °C at a heating rate of 5 °C / min, and perform heat treatment for 6 h to obtain a PtFe / C catalyst.
[0050] Pd NP The preparation method of the SC catalyst comprises the following steps: S1. Preparation of SC carrier by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 mL of tetrahydrofuran solution, stirred at room temperature for 6 hours to form a uniform mixture, and then the solvent was removed by rotary evaporation, dried, and ground to obtain a powder; the powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and a N2 atmosphere to obtain a carbonized product; the carbonized product was alkaline etched with 2 M NaOH for 3 days, and then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried at a temperature of 85 °C overnight to obtain a mesoscopic SC carrier; S2, 100 mg of the mesoscopic SC carrier obtained in S1 was dispersed in 20 mL of deionized water, and then 0.0376 mmol of PdCl2 solution was added. After ultrasonic mixing for 1 hour, the suspension was vigorously stirred for 12 hours, and the solvent was removed by rotary evaporation to obtain a precursor; S3, placing the precursor obtained in S2 in a mixed atmosphere of hydrogen and argon (the volume percentage of hydrogen is 5 vol%), heating to 450 °C at a heating rate of 5 °C / min, and heat treating for 3 h to obtain a 4 wt.% Pd nanoparticle catalyst Pd NP / SC.
[0051] Pd NP The preparation method of the SC catalyst comprises the following steps: S1. Preparation of SC carrier by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 mL of tetrahydrofuran solution, stirred at room temperature for 6 hours to form a uniform mixture, and then the solvent was removed by rotary evaporation, dried, and ground to obtain a powder; the powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and a N2 atmosphere to obtain a carbonized product; the carbonized product was alkaline etched with 2 M NaOH for 3 days, and then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried at a temperature of 85 °C overnight to obtain a mesoscopic SC carrier; S2, 100 mg of the mesoscopic SC carrier obtained in S1 was dispersed in 20 mL of deionized water, and then 0.0376 mmol of PdCl2 solution was added. After ultrasonic mixing for 1 hour, the suspension was vigorously stirred for 12 hours, and the solvent was removed by rotary evaporation to obtain a precursor; S3, placing the precursor obtained in S2 in a mixed atmosphere of hydrogen and argon (the volume percentage of hydrogen is 5 vol%), heating to 500 °C at a heating rate of 5 °C / min, and heat treating for 3 h to obtain a 4 wt.% Pd nanoparticle catalyst Pd NP / SC.
[0052] Pd NC The preparation method of the SC catalyst comprises the following steps: S1. Preparation of SC carrier by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 ml of tetrahydrofuran solution, stirred at room temperature for 6 hours to form a uniform mixture, and then the solvent was removed by rotary evaporation, dried, and ground to obtain powder; the powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and an N2 atmosphere to obtain a carbonized product; the carbonized product was alkaline etched with 2 M NaOH for 3 days, and then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried at a temperature of 85 °C overnight to obtain a mesoscopic SC carrier; S2, 100 mg of the mesoscopic SC carrier obtained in S1 was dispersed in 20 mL of deionized water, and then 0.0376 mmol of PdCl2 solution was added. After ultrasonic mixing for 1 hour, the suspension was vigorously stirred for 12 hours, and the solvent was removed by rotary evaporation to obtain a precursor; S3, placing the precursor obtained in S2 in a mixed atmosphere of hydrogen and argon (the volume percentage of hydrogen is 5 vol%), heating to 350 °C at a heating rate of 5 °C / min, and heat treating for 3 h to obtain a 4 wt.% Pd fully exposed sub-nano cluster catalyst Pd NC / SC.
[0053] The preparation method of Pd1 / SC catalyst comprises the following steps: S1. Preparation of SC carrier by cobalt-assisted carbonization of molecular precursors: In the synthesis, 2 g of 2,2-dithiophene, 2 g of SiO2 and 1 g of Co(NO3)2·6H2O were added to 150 mL of tetrahydrofuran solution, stirred at room temperature for 6 hours to form a uniform mixture, and then the solvent was removed by rotary evaporation, dried, and ground to obtain a powder; the powder was carbonized for 2 hours at a temperature of 800 °C, a heating rate of 5 °C / min and a N2 atmosphere to obtain a carbonized product; the carbonized product was alkaline etched with 2 M NaOH for 3 days, and then continuously heated with 0.5 M H2SO4 at a temperature of 90 °C for 6 hours, and then dried at a temperature of 85 °C overnight to obtain a mesoscopic SC carrier; S2, 100 mg of the mesoscopic SC carrier obtained in S1 was dispersed in 20 mL of deionized water, and then 0.0376 mmol of PdCl2 solution was added. After ultrasonic mixing for 1 hour, the suspension was vigorously stirred for 12 hours, and the solvent was removed by rotary evaporation to obtain a precursor; S3. Place the precursor obtained in S2 in a mixed atmosphere of hydrogen and argon (the volume percentage of hydrogen is 5 vol%), heat it to 250 °C at a heating rate of 5 °C / min, and perform heat treatment for 2 h to obtain a 4 wt.% Pd single atom catalyst Pd1 / SC.
[0054] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 4:4:2 to obtain a mixed reaction solvent; S2, the PtFe / C catalyst prepared in Example 1 and the commercially available Pd / C (10wt.%) catalyst were mixed in a mass ratio of 1:1 to form a combined catalyst; S3, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S4. Add 150 mL of the reaction solution in four portions of S3 and 2000 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 90 °C. The four portions are reacted for 1 h, 2 h, 3 h and 4 h respectively to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by high performance liquid chromatography analysis (hereinafter referred to as HPLC).
[0055] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 2; S2, the PtFe / C catalyst prepared in Example 1 and the commercially available Pd / C (10wt.%) catalyst were mixed in a mass ratio of 1:1 to form a combined catalyst; S3, adding p-cresol to different mixed reaction solvents in S1 respectively to obtain reaction solutions, wherein the concentration of p-cresol in the reaction solutions is 50 mmol / L; S4. Add 150 mL of the reaction solution in S3 and 2000 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 90 °C and the reaction is carried out for 4 h to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0056] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2, the PtFe / C catalyst prepared in Example 1 and the Pd NP / SC catalysts were mixed in a mass ratio of 2:1 as a combined catalyst; S3, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S4. Add 150 mL of the reaction solution in four portions of S3 and 1500 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 100 °C. The four portions are reacted for 1 h, 2 h, 3 h and 4 h respectively to obtain para-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0057] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 4; S2, the PtFe / C catalyst prepared in Example 1 and the Pd NP / SC catalysts were mixed in a mass ratio of 2:1 to serve as a combined catalyst; S3, adding p-cresol to different mixed reaction solvents in S1 respectively to obtain reaction solutions, wherein the concentration of p-cresol in the reaction solutions is 50 mmol / L; S4. Add 150 mL of the reaction solution in S3 and 1500 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 100 °C and the reaction is carried out for 4 h to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0058] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 5:3:2 to obtain a mixed reaction solvent; S2, the PtFe / C catalyst prepared in Example 1 and the Pd NC / SC catalysts were mixed in a mass ratio of 2:1 as a combined catalyst; S3, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S4. Add 150 mL of the reaction solution in four portions of S3 and 1500 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 100 °C. The four portions are reacted for 1 h, 2 h, 3 h and 4 h respectively to obtain para-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0059] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 6; S2, the PtFe / C catalyst prepared in Example 1 and the Pd NC / SC catalysts were mixed in a mass ratio of 2:1 to serve as a combined catalyst; S3, adding p-cresol to different mixed reaction solvents in S1 respectively to obtain reaction solutions, wherein the concentration of p-cresol in the reaction solutions is 50 mmol / L; S4. Add 150 mL of the reaction solution in S3 and 1500 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 100 °C and the reaction is carried out for 4 h to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0060] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 5:3:2 to obtain a mixed reaction solvent; S2, the PtFe / C catalyst prepared in Example 1 and the Pd NC / SC catalysts were mixed in a mass ratio of 2:1 as a combined catalyst; S3, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S4. Add 150 mL of the reaction solution in four portions of S3 and 1500 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The four portions are reacted at reaction temperatures of 70°C, 80°C, 90°C and 100°C for 4 h to obtain para-hydroxyaldehyde. After the reaction is completed, it is diluted and filtered, and the reactant conversion rate and product yield are determined by HPLC.
[0061] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1, mixing acetonitrile, acetic acid and water in a mass ratio of 1:1:1 to obtain a mixed reaction solvent; S2, mixing the PtFe / C catalyst prepared in Example 1 and the Pd1 / SC catalyst prepared in Example 5 in a mass ratio of 2:1 to form a combined catalyst; S3, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S4. Add six portions of 150 mL of reaction liquid in S3 and 1500 mg of combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 100 ℃. The six portions are reacted for 1 h, 2 h, 3 h, 4 h, 5 h and 6 h respectively to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0062] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1. Prepare different mixed reaction solvents, as shown in Table 9; S2, mixing the PtFe / C catalyst prepared in Example 1 and the Pd1 / SC catalyst prepared in Example 5 in a mass ratio of 2:1 to form a combined catalyst; S3, adding p-cresol to different mixed reaction solvents in S1 respectively to obtain reaction solutions, wherein the concentration of p-cresol in the reaction solutions is 50 mmol / L; S4. Add 150 mL of the reaction solution in S3 and 1500 mg of the combined catalyst in S2 into the reactor respectively. Replace the gas in the reactor with oxygen three times and maintain the pressure in the reactor at 0.5 MPa. The reaction temperature is 100 °C and the reaction is carried out for 6 h to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0063] A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 5:3:2 to obtain a mixed reaction solvent; S2, the PtFe / C catalyst prepared in Example 1 and the Pd NC / SC catalysts were mixed in a mass ratio of 2:1 as a combined catalyst; S3, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S4, add 150 mL of the reaction solution in S3 and 1500 mg of the combined catalyst in S2 into a reactor, replace the gas in the reactor with oxygen three times, maintain the pressure in the reactor at 0.5 MPa, the reaction temperature at 90 °C, react for 4 h to obtain p-hydroxyaldehyde, dilute and filter after the reaction to obtain the combined catalyst; S5. The combined catalyst obtained in S4 is cycled to carry out the catalytic reaction in S4 four times, that is, the catalyst carries out the catalytic reaction five times in total, and the reactant conversion rate and product yield of each reaction are determined by HPLC.
[0064] A continuous catalytic oxidation reaction of p-cresol to prepare p-hydroxyaldehyde comprises the following steps: S1. Ethylene glycol, acetic acid and water are mixed in a mass ratio of 4:4:2, and p-cresol is added to obtain a mixed reaction solvent, wherein the concentration of p-cresol is 50 mmol / L; S2, the PtFe / C catalyst prepared in Example 1 and the Pd NC / SC catalysts were mixed in a mass ratio of 2:1 as a combined catalyst; S3. Add 200 mL of reaction liquid in S1 and 1500 mg of combined catalyst in S2 into a 500 mL continuously stirred tank reactor. Compressed air flows through the main body of the reaction liquid through the air inlet and outlet of the reactor at a rate of 20 mL / min. The p-cresol solution is added to the reactor at a rate of 5 mL / min. The reaction liquid passes through the catalyst filtration device and is steadily withdrawn from the withdrawal pipe at a rate of 5 mL / min. The reaction temperature of the reactor is controlled at 100 °C, and mechanical stirring is turned on. It is continuously operated for 72 h. The reaction liquid at the withdrawal outlet is diluted and filtered every 2 h, and the reactant conversion rate and product yield are determined by HPLC.
[0065] Comparative Example 1 A method for preparing hydroxyaldehyde comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S3. Add 150 mL of the reaction solution in S2 and 1000 mg of the PtFe / C catalyst prepared in Example 1 into a reactor, replace the gas in the reactor with oxygen three times, maintain the pressure in the reactor at 0.5 MPa, and the reaction temperature at 90°C. React for 4 h to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0066] Comparative Example 2 A method for preparing hydroxyaldehyde comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S3, 150 mL of the reaction solution in S2 and the Pd NC500 mg of / SC catalyst was added into the reactor. The gas in the reactor was replaced with oxygen three times, and the pressure in the reactor was maintained at 0.5 MPa. The reaction temperature was 90 ℃ and the reaction was carried out for 4 h to obtain p-hydroxyaldehyde. After the reaction was completed, it was diluted and filtered, and the conversion rate of the reactants and the yield of the products were determined by HPLC.
[0067] Comparative Example 3 A method for preparing hydroxyaldehyde comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S3, 150 mL of the reaction solution in S2 and the Pd NP 500 mg of / SC catalyst was added into the reactor. The gas in the reactor was replaced with oxygen three times, and the pressure in the reactor was maintained at 0.5 MPa. The reaction temperature was 90 ℃ and the reaction was carried out for 4 h to obtain p-hydroxyaldehyde. After the reaction was completed, it was diluted and filtered, and the conversion rate of the reactants and the yield of the products were determined by HPLC.
[0068] Comparative Example 4 A method for preparing hydroxyaldehyde comprises the following steps: S1, mixing ethylene glycol, acetic acid and water in a mass ratio of 6:3:1 to obtain a mixed reaction solvent; S2, adding p-cresol to the mixed reaction solvent in S1 to obtain a reaction solution, wherein the concentration of p-cresol in the reaction solution is 50 mmol / L; S3. Add 150 mL of the reaction solution in S2 and 500 mg of the Pd1 / SC catalyst prepared in Example 5 to a reactor, replace the gas in the reactor with oxygen three times, maintain the pressure in the reactor at 0.5 MPa, and the reaction temperature at 90°C. React for 4 h to obtain p-hydroxyaldehyde. After the reaction is completed, dilute and filter, and determine the reactant conversion rate and product yield by HPLC.
[0069] Detection and analysis 1) The PtFe / C catalyst prepared in Example 1 and the Pd NP / SC catalyst, Pd prepared in Example 4 NC The Pd1 / SC catalyst and the Pd1 / SC catalyst prepared in Example 5 were characterized by TEM, XPS and XRD, respectively. The results are as follows Figures 1 to 10 shown.
[0070] from Figure 1The PtFe / C alloy nanoparticles are spherical and evenly distributed on the activated carbon support, with an average particle size of 4.7 nm. HRTEM shows an obvious lattice spacing of 0.2544 nm ( Figure 1 d), corresponding to the (111) plane of Pt in PtFe / C alloy nanoparticles.
[0071] from Figure 2 The XPS spectrum confirms that Pt and Fe elements exist on the surface of the activated carbon support ( Figure 2 a). In addition, the presence of adsorbed oxygen is also observed in the XPS measurement spectrum. The XPS fine spectra of Pt 4f and Fe 2p are shown in Figure 2. Figure 2 cd. Pt 4f spectrum ( Figure 2 c) shows two peaks, the double peaks at 71.85 and 75 eV can be attributed to Pt 0 4f 7 / 2 and Pt 0 4f 5 / 2 The electron binding energy is smaller than that of Pt 0 , the binding energy shifts to the low energy direction. Figure 2 d) The double peaks at binding energies of 711.5 and 726.3 eV can be attributed to Fe 2+ 2p 3 / 2 and 2p 1 / 2 The electron binding energy of Fe 0 , the binding energy has a certain shift toward the high energy direction; this phenomenon shows that there is an obvious electronic interaction between Pt and Fe, and there is a certain degree of transfer of Fe valence electrons to Pt, proving the formation of PtFe alloy.
[0072] from Figure 3 The analysis shows that no diffraction peaks of pure Fe and Pt nanoparticles are found in the XRD diagram. Compared with pure Pt nanoparticles, the diffraction peak position shifts to a certain degree toward a high diffraction angle. Compared with Pt nanoparticles, the PtFe alloy has a significant change in lattice spacing, which further indicates that an ordered interlayer nanoparticle alloy is formed between PtFe. Figure 4 XPS Pd 3d valence electron binding energy fine spectrum, which confirms the presence of Pd element in the supported Pd catalyst. The double peaks near 335.7 and 340.8 eV in the Pd 3d fine spectrum correspond to the Pd 0 3d 5 / 2 and 3D 3 / 2 electrons, while the binding energy peaks near 338.3 and 343.3 eV are attributed to Pd 2+ 3d 5 / 2 and 3D3 / 2 Valence electrons. Analysis of these data shows that Pd NP The 0-valence state of Pd loaded in / SC dominates the active components.
[0073] from Figure 5 The analysis shows that Pd NP In / SC, Pd nanoparticles are evenly distributed on the sulfur-carbon carrier, with an average particle size of 3.24 nm. By controlling the catalyst preparation conditions, the particle size of Pd nanoparticles can be effectively controlled.
[0074] from Figure 6 The analysis shows that Pd NP / SC nanoparticles are evenly distributed on the SC carrier, and the average particle size can be reduced to 1.66 nm. By controlling the heat treatment conditions during the catalyst preparation process, the particle size of Pd nanoparticles can be effectively controlled.
[0075] The XRD diffraction peak is closely related to the Pd particle size and loading amount. Figure 7 From the XRD diagram, it can be seen that the Pd nanoparticles, sub-nano clusters and Pd single atoms supported by SC carriers can only produce a weak diffraction peak near 40° when the size of Pd nanoparticles is small, and other peaks do not appear due to low diffraction intensity. The peak near 40° corresponds to the Pd (111) crystal plane (JCPDS NO.46-1043). As the heat treatment temperature decreases, the intensity of this characteristic diffraction peak is observed to gradually weaken, and a relatively wide weak diffraction peak is formed, which indicates that the Pd dispersion is enhanced and the size of the nanoparticles is reduced. Therefore, by controlling the loading amount of the Pd element in the carrier, the heat treatment temperature, and the form and amount of heteroatom doping of the carrier, the controllable preparation of Pd from nanoparticle size to fully exposed sub-nano clusters and Pd single atoms can be obtained.
[0076] Figure 8 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images show that the size of Pd sub-nanoclusters is reduced to less than 1 nm. Figure 8 From the analysis, we can see that most of the Pd metal atoms aggregate into sub-nanoclusters, and a small number of Pd metal atoms are confined on the carbon support in the form of single atoms (Pd1).
[0077] from Fig. 9 The XPS full spectrum analysis confirmed the presence of Pd, C, and S elements in the fully exposed sub-nanoclusters of supported Pd ( Fig. 9 a). Fig. 9 (bd) show the XPS fine spectra of various elements C, S, and Pd. Fig. 9c shows the double peaks at 164.1 and 165.3 eV in the XPS fine spectrum of S 2p valence electrons, which can be attributed to S 2p 3 / 2 and 2p 1 / 2 Electron. Pd 3d fine spectrum ( Fig. 9 The double peaks at 336.19 and 343.56 eV in d) correspond to Pd 2+ 3d 5 / 2 and 3D 3 / 2 valence electrons, while the peak near 341.68 eV can be attributed to Pd 0 3d 5 / 2 Valence electrons. The fine structure spectrum of Pd element shows that Pd 2+ The active component is dominant, and this phenomenon is attributed to the interaction between the surface Pd element and the S element in the carrier. This result corresponds to the Pd mainly existing in the form of sub-nano clusters observed in the HAADF-STEM image. By further controlling the loading amount of the Pd element in the carrier, the heat treatment temperature, and the form and amount of heteroatom doping of the carrier, the catalyst preparation method involved in this invention can make Pd exist in the form of Pd single atoms on the doped carbon carrier, such as Fig.10 As shown in the figure, HAADF-STEM image characterization shows that the confined Pd single atoms are uniformly distributed on the surface of the mesoporous S-doped C material, and no obvious sub-nano clusters of Pd appear on the surface of the carrier. NC Or nanoparticles P NP , and the Pd element is evenly distributed on the entire SC support.
[0078] 2) Analysis of p-cresol conversion rate and p-hydroxyaldehyde yield The conversion rate of p-cresol and the yield of p-hydroxyaldehyde at different reaction times in Example 6 were determined by HPLC. The results are shown in Table 1.
[0079] Table 1: p-Cresol conversion and p-hydroxyaldehyde yield at different reaction times under the action of PtFe / C and commercially available Pd / C combined catalysts From the analysis in Table 1, it can be seen that when the PtFe / C catalyst prepared in Example 1 is used in combination with the commercially available Pd / C catalyst, the conversion rate of p-cresol and the yield of p-hydroxyaldehyde gradually increase with the extension of the reaction time. At the reaction time of 4 h, the reactants have reacted completely, and the product yield reaches 98.1%.
[0080] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde in different mixed reaction solvents in Example 7 were determined by HPLC. The results are shown in Table 2.
[0081] Table 2: p-Cresol conversion and p-hydroxyaldehyde yield under the action of PtFe / C and commercially available Pd / C combined catalysts in different mixed solvents As can be seen from Table 2, in mixed solvents of different proportions and compositions, the yield of p-hydroxyaldehyde is different, indicating that the composition of the mixed solvent has an important influence on the reaction. This example illustrates that the use of the best mixed solvent composition is conducive to the safe, stable and efficient catalytic oxidation of p-cresol to prepare p-hydroxyaldehyde. The p-cresol conversion rate and the p-hydroxyaldehyde yield under different reaction times in Example 8 were measured by HPLC, and the results are shown in Table 3.
[0082] Table 3: PtFe / C, Pd NP / SC(450 o C heat treatment preparation) p-cresol conversion rate and p-hydroxyaldehyde yield under different reaction times of combined catalyst From the analysis in Table 3, it can be seen that the Pd NP The / SC nanoparticle catalyst and PtFe / C constructed a combined catalyst. After participating in the catalytic reaction for 3 hours, the reactants were completely reacted. As the reaction time increased, the product yield could reach 90.5% in 4 hours.
[0083] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde in the mixed solvents of different proportions under the action of the combined catalyst in Example 9 were determined by HPLC. The results are shown in Table 4.
[0084] Table 4: PtFe / C, Pd NP p-Cresol conversion and p-hydroxyaldehyde yield in different mixed solvents over the action of SC / SC combination catalyst From the analysis in Table 4, it can be seen that the p-hydroxyaldehyde yields are different in mixed solvents with different proportions and compositions. The selection of a mixed solvent with a suitable proportion is conducive to the efficient and stable conversion of p-cresol to p-hydroxyaldehyde under the action of the combined catalyst.
[0085] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde at different reaction times under the action of the combined catalyst in Example 10 were determined by HPLC. The results are shown in Table 5.
[0086] Table 5: PtFe / C, Pd NC Conversion rate of p-cresol and yield of p-hydroxyaldehyde at different reaction times under the action of SC / SC combination catalyst From the analysis in Table 5, we can see that the Pd NCThe / SC sub-nanocluster catalyst and PtFe / C constitute a combined catalyst. After participating in the catalytic reaction for 3 h, the reactants are completely reacted. As the reaction time increases, the product yield can reach 99.8% in 4 h.
[0087] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde in different mixed solvents under the action of the combined catalyst in Example 11 were determined by HPLC. The results are shown in Table 6.
[0088] Table 6: PtFe / C, Pd NC p-Cresol conversion and p-hydroxyaldehyde yield in different mixed solvents over the action of SC / SC combination catalyst From the analysis of Table 6, it can be seen that the p-hydroxyaldehyde yields are different in mixed solvents with different proportions and compositions. The selection of a mixed solvent with a suitable proportion is conducive to the efficient and stable conversion of p-cresol to p-hydroxyaldehyde under the action of a combined catalyst.
[0089] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde of the combined catalyst in Example 12 at different reaction temperatures were determined by HPLC. The results are shown in Table 7.
[0090] Table 7. PtFe / C, Pd NC Conversion rate of p-cresol and yield of p-hydroxyaldehyde at different reaction temperatures under the action of / SC combined catalyst From the analysis in Table 7, it can be seen that at different reaction temperatures, the same combination of catalysts participates in the reaction, and the effects are obviously different. With the increase of temperature, the conversion rate of p-cresol gradually increases, and the yield of p-hydroxyaldehyde also gradually increases. When the reaction temperature reaches 100°C, the conversion rate of p-cresol and the yield of p-hydroxyaldehyde reach the highest value, indicating that the increase of reaction temperature is conducive to increasing the reaction rate, and the product selectivity will not decrease.
[0091] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde at different reaction times under the action of the combined catalyst in Example 13 were determined by HPLC. The results are shown in Table 8.
[0092] Table 8: p-cresol conversion and p-hydroxyaldehyde yield at different reaction times under the action of PtFe / C and Pd1 / SC combined catalysts From the analysis in Table 8, it can be seen that the combined catalyst consisting of the Pd1 / SC single atom catalyst obtained by heat treatment at 250 °C and the PtFe / C catalyst has a reactant conversion rate of 96.7% and a product yield of 78.9% after participating in the catalytic reaction for 6 h.
[0093] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde in different mixed solvents under the action of the combined catalyst in Example 14 were determined by HPLC. The results are shown in Table 9.
[0094] Table 9: p-Cresol conversion and p-hydroxyaldehyde yield in different mixed solvents under the action of PtFe / C and Pd1 / SC combined catalysts From the analysis in Table 9, it can be seen that the conversion rate of p-cresol and the yield of p-hydroxyaldehyde are different in different mixed solvents. This example shows that the use of the best mixed solvent composition is conducive to the safe, stable and efficient catalytic oxidation of p-cresol to prepare p-hydroxyaldehyde.
[0095] The conversion rate of p-cresol and the yield of p-hydroxyaldehyde after 5 repeated cycles of the combined catalyst in Example 15 were determined by HPLC. The results are as follows: Fig.11 shown.
[0096] from Fig.11 It can be seen from the analysis that in the 5 cycle experiments, the combined catalyst still maintained a high conversion rate of p-cresol and a high yield of p-hydroxyaldehyde under the optimal conditions, showing excellent stability, thereby proving that the metal active components of the combined catalyst of the present invention are not easy to be lost and the active sites are not easy to be poisoned.
[0097] Determination of PtFe / C and Pd in Example 16 by HPLC NC The results of the reactant conversion rate and product yield at the outlet of the continuous catalytic oxidation process of the / SC combined catalyst are as follows: Fig.12 shown.
[0098] from Fig.12 The analysis shows that in a normal pressure continuous tank reactor, with continuously flowing air as the oxidant, the catalytic system further achieves the continuous production of p-cresol with high selectivity to prepare p-hydroxyaldehyde. During the continuous oxidation process, the selectivity of the target product p-hydroxyaldehyde at the reactor outlet remained above 91% within 72 hours, and the catalyst did not show obvious deactivation during the continuous 72 hours of use.
[0099] The results of HPLC determination were as follows: NC / SC catalyst, Pd alone was used in comparative example 3 NP The conversion rate of p-cresol and the yield of p-hydroxyaldehyde using the Pd1 / SC catalyst and the Pd1 / SC catalyst alone in Control Example 4 are shown in Table 10.
[0100] Table 10 PtFe / C catalyst or Pd NC p-Cresol conversion and p-hydroxyaldehyde yield over SC catalyst From the analysis of Table 10, it can be seen that the use of PtFe / C catalyst or Pd NC / SC catalyst or Pd NP / SC catalyst or Pd1 / SC catalyst, the conversion rate of p-cresol and the yield of p-hydroxyaldehyde are both very low, which proves that the combined catalyst of the present invention has a synergistic effect.
[0101] In summary, the combined catalyst of the present invention can efficiently activate molecular oxygen, realize the conversion of p-cresol to p-hydroxyaldehyde with high selectivity, avoid the self-polymerization of phenol oxygen ring into uncontrollable polymers, and reduce the production of tar substances that may poison the active center of the catalyst. The reaction conditions are simple and easy to control. Under low pressure (0.5 MPa) and temperature (90-100 ° C), and in a short time (3-6 hours), the highly selective preparation of p-hydroxyaldehyde by catalytic oxidation of p-cresol under non-alkaline conditions is achieved. In addition, the combined catalyst can still maintain a high p-cresol conversion rate and p-hydroxyaldehyde yield during repeated use, showing excellent stability.
[0102] The present invention provides a method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkali conditions, which is carried out in a stable and safe mixed solvent system without methanol and soluble alkali, and realizes efficient and convenient preparation of PtFe / C catalysts and Pd single atoms Pd1 / SC and Pd sub-nanoclusters Pd with controllable loading and particle size. NC / SC, Pd nanoparticles NP / SC catalyst. Through the adsorption regulation at the active sites of each intermediate and the synergistic effect of each oxidation step, the method activates molecular oxygen to oxidize p-cresol under completely alkali-free conditions, which not only reduces the requirements and risks for reaction equipment, but also reduces the cost of subsequent product separation and purification, and avoids the generation of a large amount of low-value waste salt. It has significant promotion and application potential in the field of p-hydroxyaldehyde preparation technology.
[0103] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.
Claims
1. A combined catalyst, characterized in that: The catalyst is composed of a PtFe / C catalyst and a Pd / C catalyst or a PtFe / C catalyst and a Pd / SC catalyst.
2. The combined catalyst according to claim 1, characterized in that The PtFe / C catalyst is a nano alloy catalyst with ordered interlayers; And / or, the Pd / SC catalyst is selected from Pd1 / SC catalyst, Pd NC / SC catalyst and Pd NP / at least one of SC catalysts; And / or, the mass ratio of the PtFe / C catalyst to the Pd / C catalyst is 5:1 to 1:5; And / or, the mass ratio of the PtFe / C catalyst to the Pd / SC catalyst is 5:1 to 1:
5.
3. The method for preparing the combined catalyst according to any one of claim 1 or claim 2, characterized in that: The following steps are involved: Dissolving iron salt in water to obtain an iron salt solution; dissolving a pyridine compound in an organic solvent to obtain a pyridine solution; mixing the iron salt solution and the pyridine solution to obtain a complex solution; Adding platinum acid solution into the complex solution to obtain a PtFe compound; The PtFe compound is dispersed in water, and then a carbon source is added, mixed and dried, and subjected to a first heat treatment to obtain a PtFe / C catalyst; mixing a PtFe / C catalyst with a Pd / C catalyst to obtain a combined catalyst; and / or, comprising the steps of: Mesoscopic SC supports were prepared by cobalt-assisted carbonization of molecular precursors; The mesoscopic SC support is dispersed in water and a palladium salt solution is added to obtain a precursor; The precursor is subjected to a second heat treatment to obtain a Pd / SC catalyst.
4. The preparation method according to claim 3, characterized in that: The pyridine compound is at least one selected from pyridine, 2,2'-bipyridine and 2,2':6',2''-tripyridine; And / or, the iron salt is at least one selected from ferrous sulfate, ferrous sulfate heptahydrate, ferrous chloride, ferrous nitrate and ferrous acetylacetonate; And / or, the carbon source is selected from activated carbon or a carbon material carrier; And / or, the platinum acid solution is selected from at least one of a chloroplatinic acid solution, a hexahydrate chloroplatinic acid solution and a potassium chloroplatinate solution; And / or, the organic solvent is selected from ethanol; And / or, the palladium salt is selected from at least one of palladium chloride, palladium nitrate and palladium acetate.
5. The preparation method according to claim 3, characterized in that: The temperature of the first heat treatment is 500°C to 900°C, the heating method is programmed heating, and the heating rate is 5°C / min to 10°C / min; the time of the first heat treatment is 3 h to 6 h; the first heat treatment is carried out in a mixed atmosphere of hydrogen and inert gas; And / or, the temperature of the second heat treatment is 250°C-500°C, the heating method is programmed heating, and the heating rate is 5°C / min-10°C / min.
6. The preparation method according to claim 3, characterized in that: The preparation method of the mesoscopic SC carrier comprises the following steps: adding 2,2-dithiophene, silicon dioxide and cobalt salt to a tetrahydrofuran solution, mixing and drying to obtain powder; heating the powder for carbonization, alkaline etching and a third heating treatment, and drying to obtain the mesoscopic SC carrier.
7. Use of the combined catalyst according to any one of claim 1 or claim 2, characterized in that: The combined catalyst is used for catalyzing p-cresol to prepare p-hydroxyaldehyde under non-alkaline conditions.
8. A method for preparing p-hydroxyaldehyde by catalytic oxidation of p-methylphenol under non-alkaline conditions, characterized in that: The following steps are involved: Add p-cresol and the combined catalyst according to claim 1 or claim 2 to a mixed solvent that does not contain methanol and soluble alkali, and heat the mixed reactants under an oxygen or air pressure of 0.3 Mpa to 0.8 Mpa to obtain p-hydroxyaldehyde.
9. The preparation method according to claim 8, characterized in that: The methanol-free organic solvent is selected from at least one of ethylene glycol, acetic acid and acetonitrile.
10. A para-hydroxyaldehyde, characterized in that The method is as claimed in claim 8 or claim 9.
Citation Information
Patent Citations
Composite material in atomic dispersion, preparation method thereof and application thereof
CN109759133A
Catalytic system for catalytic oxidation of p-cresol under alkali-free condition and application
CN114887619A
Process for the production of hydroxy-substituted aromatic aldehydes and ketones
WO2001009072A1